Mitochondrial PITRM1 peptidase loss-of-function in childhood cerebellar atrophy. Issue 9 (15th May 2018) - Langer, Yeshaya; Aran, Adi; Gulsuner, Suleyman; Abu Libdeh, Bassam; Renbaum, Paul; Brunetti, Dario; Teixeira, Pedro-Filipe; Walsh, Tom; Zeligson, Sharon; Ruotolo, Roberta; Beeri, Rachel; Dweikat, Imad; et al.
Abstract : Objective: To identify the genetic basis of a childhood-onset syndrome of variable severity characterised by progressive spinocerebellar ataxia, mental retardation, psychotic episodes and cerebellar atrophy. Methods: Identification of the underlying mutations by whole exome and whole genome sequencing. Consequences were examined in patients' cells and in yeast. Results: Two brothers from a consanguineous Palestinian family presented with progressive spinocerebellar ataxia, mental retardation and psychotic episodes. Serial brain imaging showed severe progressive cerebellar atrophy. Whole exome sequencing revealed a novel mutation: pitrilysin metallopeptidase 1 ( PITRM1 ) c.2795C>T, p.T931M, homozygous in the affected children and resulting in 95% reduction in PITRM1 protein. Whole genome sequencing revealed a chromosome X structural rearrangement that also segregated with the disease. Independently, two siblings from a second Palestinian family presented with similar, somewhat milder symptoms and the same PITRM1 mutation on a shared haplotype. PITRM1T931M carrier frequency was 0.027 (3/110) in the village of the first family evaluated, and 0/300 among Palestinians from other locales. PITRM1 is a mitochondrial matrix enzyme that degrades 10–65 amino acid oligopeptides, including the mitochondrial fraction of amyloid-beta peptide. Analysis of peptide cleavage activity by the PITRM1T931M protein revealed a significant decrease in the degradation capacity specifically of peptides ≥40 amino acids. Conclusion: PITRM1T931M results in childhood-onset recessive cerebellar pathology. Severity of PITRM1 -related disease may be affected by the degree of impairment in cleavage of mitochondrial long peptides. Disruption and deletion of X linked regulatory segments may also contribute to severity.